Reinforcing the Functionality of Mononuclear Phagocyte System to Control Tuberculosis - Pahari, Susanta; Kaur, Gurpreet; Negi, Shikha; Aqdas, Mohammad; Das, Deepjyoti K.; Bashir, Hilal; Singh, Sanpreet; Nagare, Mukta; Khan, Junaid; Agrewala, Javed N. (Frontiers in Immunology, 2018)
The mononuclear phagocyte system (MPS) constitutes dendritic cells (DCs), monocytes and macrophages. This system contributes to various functions that are essential for maintaining homeostasis, activation of innate immunity and bridging it with the adaptive immunity. Consequently, MPS are highly important in bolstering immunity against the pathogens. Although, MPS are the frontline cells in destroying Mycobacterium tuberculosis (Mtb), yet the bacterium prefers to reside in the hostile environment of macrophages. Therefore, it may be very interesting to study the struggle between Mtb and MPS to understand the outcome of the disease. In an event when MPS predominates Mtb, the host remains protected. In contrast, the situation becomes devastating when the pathogen tames and tunes the host MPS, which ultimately culminates into tuberculosis (TB). Hence, it becomes extremely crucial to reinvigorate MPS functionality to overwhelm Mtb and eliminate it. In the current article, we discuss the strategies to bolster the function of MPS by exploiting the molecules associated with the innate immunity and highlight the mechanisms involved to overcome the Mtb induced suppression of host immunity. In future, such approaches may provide an insight to develop immuno-therapeutics to treat TB.